COMMUNICATIVE TABOOS AND EUPHEMIZATION STRATEGIES IN THE RUSSIAN AND UZBEK LANGUAGES: A PRAGMALINGUISTIC APPROACH - Жабборова Наргиза (Web of Journals Publishing, 2025)
This study is devoted to the study of the phenomenon of communicative taboos and ways of their linguistic transformation within the framework of Russian and Uzbek linguistic cultures. Special attention is paid to euphemization as a universal mechanism that allows to soften or bypass the direct naming of topics that go beyond the permissible in speech communication. The analysis is based on the corpus of fiction, journalistic and colloquial texts, as well as the data of empirical questionnaires. identification of differences in the strategies of verbal politeness, the degree of stylistic masking of taboo vocabulary and the cultural conditioning of euphemisms in the Russian and Uzbek languages. The results obtained make it possible to clarify the functional features of euphemism as part of the pragmalinguistic norm in national languages and expand the understanding of the socio-cultural mechanisms of speech regulation.
Keywords: Communicative taboo, euphemization, pragmalinguistics, speech politeness, cultural norm, Russian language, Uzbek language, sociolinguistics.